<span>2(х+1,2)=2,7-х
2х+2,4=2,7-х
2х+х=2,7-2,4
3ч=0,3
х=0,3/3
х=0,1
</span>
<span>х:1,8= 2 1/9: 6 1/3
</span>х:1,8 = 19/6 : 19/3
х:1,8 = 19/6 * 3/19
<span>х:1,8 = 3/6
</span><span>х:1,8 = 1,2
</span>х:1,8 = 0,5
х=0,5*1,8
х = 0,9
<span>0,6-1,6(х-4)=3(7-0,4х)
0,6-1,6х+6,4=21-1,2х
-1,6х+1,2х=21</span>-<span>0,6</span>-6,4
-0,4х=14
х=14:-0,4
х=-35
2,3х+2,5х+31=67
4,8х +31=67
4,8х=67-31
4,8х=36
х=36:4,8
х=7,5
Tg(π/4) = 1
tg(π/3) = √3/3
3tg(π/4)*tg(π/3) = 3*1*√3/3 = √3
С+175=12000÷24
с+175=500
с=500-175
с=325